Digital Storytelling for Sustainability Education: Examining Its Impact on Pro-Environmental Behavior - Rina Farah; Zain Nizam; Rahmi Setiawati (International Journal of Educational Narratives, 2026)
Background. Narrative communication offers promising alternatives, yet systematic understanding of how digital storytelling specifically promotes sustained pro-environmental behaviors remains underdeveloped. Purpose. This study investigated whether participatory creation of digital environmental narratives leads to stronger and more sustained pro-environmental behavior change compared to passive narrative consumption or information-based education, while also examining the mediating roles of psychological mechanisms such as narrative transportation and environmental self-efficacy Method. Mixed-methods experimental design randomly assigned 228 undergraduate students to participatory creation, passive consumption, or information-based control conditions, measuring pro-environmental behaviors, attitudes, self-efficacy, and psychological distance across baseline, immediate post-intervention, 3-month, and 6-month follow-ups. Results. Participatory creation produced significantly greater behavior change (33% increase maintained at 6-month follow-up) compared to passive consumption (12% increase) and control (0% increase). Environmental self-efficacy mediated 61% of participatory creation effects while narrative transportation mediated 73% of passive consumption effects. Conclusion. This research demonstrates that creating digital environmental narratives produces superior behavior change compared to consuming narratives through distinct psychological mechanisms emphasizing capability-building over persuasion.